(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
The results of this study are to identify the factors determining the adherence of doctor staff in basic line public hospitals in Vietnam, including: (1) Payment (2) Opportunities for Training and promoting, (3) working environment, (4) Welfare (5) reward, (6) labor relationship. Qualitative and quantitative research methods are used and 450 personnel working in 8 district hospitals in Dong Nai and Binh Duong are also surveyed. The research results are also the basis for proposing solutions to maximize the adherence of doctor staff in basic line public hospitals in Vietnam.